Leitura semiótica e reconstrução histórica: Análise de imagens da manifestação pela manutenção da UNESP - de Oliveira, Édison Trombeta [UNESP]; Ribeiro, Arilda Inês Miranda [UNESP] (My University, 2014)
It is known the importance of the pictures in historical reconstructions and as a memory trigger. This article analyzed semiotically, by Peirce (2000) and Bakhtin (1990), three photographs of the Folha de S. Paulo, of 1976, about the manifestation to the upkeep of Unesp from Presidente Prudente, reaction at the cut in the number of courses in the city and foreclosure risk activities, traumatizing moment according to participants. It's denoted the Semiotic Analysis serves greatly in obtaining data on historical reconstructions.
Semiotic way of reading and historical reconstruction: Image analysis of the manifestation to the upkeep of UNESP
Keywords: History of institutions school; Photograph; Semiotic analysis; Unesp